The Effect of Leadership, Motivation and Work Discipline on Employee’s Performance: A Case Study of Husky CNOOC Madura Limited (HCML) - Haryanto, Bambang; Idris, Muhammad; Choiriyah, Choiriyah (International Journal of Business, Management and Economics, 2023)
This study aims to determine the influence of leadership, motivation and work discipline on the performance of Husky CNOOC Madura Limited (HCML) employees. The object of this research is the employees of Husky Company CNOOC Madura Limited (HCML). The population in this study amounted to 211 employees, with a total sample of 139 Husky Company CNOOC Madura Limited (HCML) employees. The sampling technique used is probability sampling. The data used is primary data. Data collection techniques by distributing questionnaires. The data analysis used is the instrument test, the classical assumption test and the multiple linear regression test using a significant level of 5%. The results showed a significant influence of leadership, motivation, and work discipline on the performance of Husky CNOOC Madura Limited (HCML) employees. It indicates a significant influence of leadership on the performance of Husky CNOOC Madura Limited (HCML) employees. Shows that there is a significant influence of motivation on the performance of Husky CNOOC Madura Limited (HCML) employees. It indicates a significant effect of work discipline on the performance of Husky CNOOC Madura Limited (HCML) employees. The variables of leadership, motivation, and work discipline can explain changes in employee performance by 57.2%, and the remaining 42.8% is explained by other variables not included in this study.).